POLITIK HUKUM ISLAM DALAM UNDANG-UNDANG JAMINAN PRODUK HALAL : (Analisis Terhadap Program Sertifikasi Halal Gratis 2022 di Sumatera Utara) - Evriza Noverda Nasution (International Journal Mathla’ul Anwar of Halal Issues, 2023)
This research was written regarding the politics of Islamic law in the law on halal product namely which is in accordance with the definition put forward by Mahfud MD in his book on legal politics in Indonesia, namely "legal policy or official (policy) lines regarding laws that will be enforced either by new legal actions as well as by changing old laws, in order to achieve state goals" (.MD, Depok, p. 1), from this definition this research begins which will discuss the politics of Islamic law in the law on halal product guarantees (UU No. 33 of 2014) analysis of the role of halal assistants in the Sehati 2022 program. As stated in the law on halal product guarantees that all products circulating in Indonesia must be halal certified, the provisions of this law on halal product guarantees also require the existence of a special body tasked with determining the halalness of food, medicines and cosmetics which in matters this is called the Halal Product Assurance Organizing Agency, abbreviated as BPJPH which is under the auspices of the ministry of religion, currently BPJPH is conducting a free halal certification program (sehati program) for micro, small and medium enterprises (MSMEs) where a halal companion is someone who has been a companion from the start for MSME business actors in the process of applying for halal certification on their products. Departing from the description above, the authors are interested in conducting research on how Islamic legal politics is in the law on halal product guarantees, how is the Sehati program implemented by BPJPH and what are the roles of Halal assistants in the Sehati 2022 program, the research method used is the normative research method - empirical where the author conducts an analytical study based on applicable laws and research on business actors and also halal assistants on how the role of halal assistants at each stage of this free halal certification program is carried out. The results of the research conducted show that politically the law on halal product guarantees which was ratified by the government with all the dynamics on it is a must, where before this law existed, which became the permanent legal umbrella for MUI as the executor of the halal certification process at that time not yet strong and the form of the presence of this halal certification law makes for a division of labor between the Ministry of Religion, in this case BPJPH and other agencies in the process of halal certification and this free halal certification program is one manifestation of the development and development of the product halalization program in Indonesia.